Denervation Dynamics After Intramuscular BNT Injection in Patients With Focal Spasticity Monitored by MRI and Dynamometry–a Blinded Randomized Controlled Pilot Study - Macher, Stefan; Unger, Ewald; Zalaudek, Martin; Weber, Michael; Kranz, Gottfried; Kranz, Georg; Kasprian, Gregor; Sycha, Thomas (Frontiers in Neurology, 2021)
Introduction: Botulinumtoxin associated muscle denervation (BNTMD) can be detected by magnet resonance imaging (MRI), MRI may provide further insights into the exact timeline of BNTMD and the potential impact and timing of physical exercise. We aimed to assess the time interval until detection of BNTMD by MRI and whether immediate physical exercise after intramuscular BNT injection has a measurable effect on clinical parameters and the intramuscular denervation dynamics illustrated by MRI. Materials and Methods: Eleven age-matched patients were randomized to an “exercise” or “no-exercise” group. Eighty mouse-units of incobotulinumtoxin were injected into the spastic biceps muscle. MRI of the injected region, hand-held dynamometry of elbow flexor strength and clinical rating scales (mAS, CGI-I) were conducted in predefined intervals. Results: We could not detect BNTMD within 24 h but 7 days after injection independent of group allocation (exercise n = 6, no-exercise n = 5). Denervation signs were more diffuse and spread into adjacent muscles in patients having received exercise. We could not detect differences concerning clinical measures between the two groups. Conclusions: Physical exercise might influence BNTMD dynamics and promote propagation of T2-MR muscle denervation signs from the injected site into adjacent muscles. Trial registration:clinicaltrialsregister.eu, Identifier 2017-003117-25.